Cemiplimab in advanced cutaneous squamous cell carcinoma. Issue 6 (8th November 2021) - Naik, Piyu Parth
Abstract: Cemiplimab, a high‐affinity, highly potent human monoclonal antibody that binds to the programmed death‐1 (PD‐1)/programmed death ligand‐1 (PD‐L1) receptor, is the only drug to attain Food and Drug Administration (FDA) approval and marketing authorization from the European Commission for use in patients with metastatic and locally advanced cutaneous squamous cell carcinoma (CSCC) who are not candidates for curative surgery or curative radiation therapy as a first‐ or later‐line treatment. In pivotal phase II clinical testing, cemiplimab showed rapid and substantial antitumor efficacy and acceptable safety. This systematic review was aimed at evaluating the efficacy and safety of cemiplimab in patients with advanced CSCC. To this end, I reviewed EMBASE, MEDLINE, PubMed, and clinical trial registries/databases by using the following keywords alone or in combination: "cemiplimab, " "Libtayo, " "cutaneous squamous cell carcinoma, " "REGN2810, " and "SER439684." Cemiplimab showed clinical efficacy and considerable safety and was associated with low rates of treatment discontinuation (7%) and death (3%). However, the current recommendation is primarily based on only phase II clinical testing due to the absence of an approved comparator agent.